A retrospective analysis of the perceived impact of the COVID-19 pandemic on systemic barriers to success for university student parents - Franklin, Khadeejah T.; Saval, Alexa J.; Cafer, Anne M.; Reinemann, Dana N. (Frontiers in Education, 2024)
Introduction Student parents, both undergraduate and graduate, face the difficult task of balancing their studies and raising children, and they are a population often neglected or forgotten by higher education administration. The COVID-19 pandemic enhanced already present issues student parents face through the implementation of virtual schooling, increased daycare costs and closings, staying home with sick children, and a lack of local support system, among others. Further, many student parents are graduate students who are performing research that requires physical campus space and equipment to fulfill their educational requirements, and their research progress come to a halt when the country locked down. Methods This study explored the struggles student parents faced prior to the COVID-19 pandemic, what issues the pandemic exacerbated, and what new problems have since arisen. Participants completed surveys assessing the consequences of being a student parent during the pandemic, coping resources available to them, the effect of being a student parent during the pandemic on their mental health, and demographic information. Results Prevalent themes include substantial declines in mental health, feelings of inadequacy in regards to both their parenting and academic abilities compared to their non-student parent peers, and a striking lack of resources or acknowledgement from their institution. Discussion The survey results are framed within the social-ecological model to better understand the systemic implications of student parent conditions. Finally, we formulate a set of recommendations to higher education administrations to inform them about the unique struggles student parents face and suggest strategies for mitigation.